2015
DOI: 10.1002/pola.27701
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of poly(DMC‐co‐HPA) hydrogels via infrared laser ignited frontal polymerization and their adsorption–desorption switching performance

Abstract: In this work, we report a versatile infrared laser ignited frontal polymerization technique for the fabrication of a series of poly(DMC-co-HPA) hydrogels (DMC 5 methacryloxyethyltrimethyl ammonium chloride, HPA 5 hydroxypropyl acrylate). Because the method is based on the exothermic reaction, no further energy is required in the reaction once it is initiated. Moreover, we have found the polymerization process is a pure frontal polymerization model without involving any other reaction process. The dependence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…The chelation of metal ions with carboxyl units and hydrogel networks render them distinct advantages for carboxyl groups to capture the guest metal ions. While under acidic conditions, the protonation of carboxyl groups plays a key role in metal ion desorption. , The adsorption/desorption behavior could be easily switched by regulating the pH value, allowing the repeated cycle of hydrogels toward removal of metal ions, as illustrated in Figure c,d.…”
Section: Resultssupporting
confidence: 87%
“…The chelation of metal ions with carboxyl units and hydrogel networks render them distinct advantages for carboxyl groups to capture the guest metal ions. While under acidic conditions, the protonation of carboxyl groups plays a key role in metal ion desorption. , The adsorption/desorption behavior could be easily switched by regulating the pH value, allowing the repeated cycle of hydrogels toward removal of metal ions, as illustrated in Figure c,d.…”
Section: Resultssupporting
confidence: 87%
“…When the monomer ionic degree was 10%, the release ratio reached the peak. This indicated that the intermolecular forces between the chains and the osmotic pressure had a profound effect on the release performances of the microspheres 38,39 . The presence of ions in the chain of microspheres and absorbed Na 2 SiO 3 caused the osmotic pressure difference between the polymeric network and the external solution increasing, to increase, resulting in an increase in the diffusion of Na 2 SiO 3 in water.…”
Section: Resultsmentioning
confidence: 98%
“…This indicated that the intermolecular forces between the chains and the osmotic pressure had a profound effect on the release performances of the microspheres. 38,39 The presence of ions in the chain of microspheres and absorbed Na 2 SiO 3 caused the osmotic pressure difference between the polymeric network and the external solution increasing, to increase, resulting in an increase in the diffusion of Na 2 SiO 3 in water. Meanwhile, the hydrolysis of ester groups in the alkaline solution of sodium silicate promoted the release of silicate radical ions, because the quaternary ammonium cation ( N + (CH 3 ) 2 Cl − ) connected with the main chains through the ester group ( COOCH 2 CH 2 ).…”
Section: Monomer Ionic Degreesmentioning
confidence: 99%
“…The above mentioned peaks were observed on the spectra of P(AM-co-HPA-co-NVP) gel indi-cates the successful copolymerization of AM, HPA and NVP via FP. [35,36]…”
Section: Fabrication Of Poly(am-co-hpa-co-nvp) Gels Via Fp At Centimeter-scalementioning
confidence: 99%